Predicted COVID-19 molecular effects on endometrium reveal key dysregulated genes and functions. (7th October 2022) - Henarejos-Castillo, I; Devesa-Peiro, A; de Miguel-Gomez, L; Sebastian-Leon, P; Romeu, M; Aleman, A; Molina-Gil, C; Pellicer, A; Cervello, I; Diaz-Gimeno, P
Abstract: COVID-19 exerts systemic effects that can compromise various organs and systems. Although retrospective and in silico studies and prospective preliminary analysis have assessed the possibility of direct infection of the endometrium, there is a lack of in-depth and prospective studies on the impact of systemic disease on key endometrial genes and functions across the menstrual cycle and window of implantation. Gene expression data have been obtained from (i) healthy secretory endometrium collected from 42 women without endometrial pathologies and (ii) nasopharyngeal swabs from 231 women with COVID-19 and 30 negative controls. To predict how COVID-19-related gene expression changes impact key endometrial genes and functions, an in silico model was developed by integrating the endometrial and COVID-19 datasets in an affected mid-secretory endometrium gene co-expression network. An endometrial validation set comprising 16 women (8 confirmed to have COVID-19 and 8 negative test controls) was prospectively collected to validate the expression of key genes. We predicted that five genes important for embryo implantation were affected by COVID-19 (downregulation of COBL, GPX3 and SOCS3, and upregulation of DOCK2 and SLC2A3 ). We experimentally validated these genes in COVID-19 patients using endometrial biopsies during the secretory phase of the menstrual cycle. The results generally support the in silico model predictions, suggesting that the transcriptomic landscape changes mediated by COVID-19 affect endometrial receptivity genes and key processes necessary for fertility, such as immune system function, protection against oxidative damage and development vital for embryo implantation and early development.